Oral Health and Its Aetiological Role in Behçet's Disease - Mumcu, Gonca; Fortune, Farida (Frontiers in Medicine, 2021)
Behçet's disease (BD) as a chronic multi-systemic inflammatory disorder characterized by oro-genital ulcers, cutaneous manifestations, ocular, vascular, neurologic and gastrointestinal involvement. The interactions among genetic background (HLA-B51), infectious agents, hormones and immune dysregulation are implicated in the pathogenesis of the disease. Environmental factors triggering immune responses may activate clinical manifestations in genetically susceptible individuals. Since oral health forms the basis of all dental and general health, it is an essential and important component of both Dentistry and Medicine. Oral ulcers are the most common clinical manifestation of oral health. They may act as an infective and immune trigger within the oral environmental to affect in the pathogenesis of BD. In this review, complex interactions among oral microbiome and immune responses as well as oral ulcers and disease course are discussed in the context of etiologic role of oral health.